Procedure‐related readmissions following endoscopic retrograde cholangiopancreatography in a liver transplant cohort - Jennifer Gu; Leonardo Zorron Cheng Tao Pu; Jonathan Ng; Kim H Be; Rhys Vaughan; Sujievvan Chandran; Marios Efthymiou (JGH Open)
Abstract Background and Aim Data on post‐endoscopic retrograde cholangiopancreatography (ERCP) adverse events and readmission rates in liver transplantation (LT) patients remain scarce. This study determined the 30‐day procedure‐related readmission rate following ERCP in an LT cohort at an Australian tertiary academic center. Methods All unplanned readmissions within 30 days following ERCP in orthotopic LT patients between December 2012 and August 2021 were retrospectively identified. Demographic data, procedure variables, and readmission characteristics were also collected. Results Forty‐five procedure‐related readmissions were identified (3.3%) from a total of 1369 ERCP procedures. This included 33 cases of cholangitis (2.4%), 7 cases of nonspecific abdominal pain (0.5%), 5 cases of mild post‐ERCP pancreatitis (0.5%), and 3 cases of bleeding (0.2%). No procedure‐related mortality was observed. Conclusion The procedure‐related readmission rate following ERCP in this LT cohort was 3.3%, which is likely lower than comparable studies carried out on the overall population.